Comparative tolerance and survival of scirpus grossus and lepironia articulata in real crude oil sludge - Shilatul Najwa Binti Sharuddin, Siti; Rozaimah Sheikh Abdullah, Siti; Abu Hasan, Hassimi; Razi Othman, Ahmad (International Journal of Engineering and Technology, 2019)
Phytoremediation, a green technology that utilizes plants to degrade and remove contaminants from environment, has become a promising treatment for removing many types of contaminants including hydrocarbon pollutants. This technology is potentially efficient, much cheaper and more environmentally friendly than the conventional mechanical clean-up methods. The main objectives of the current study were to evaluate the phytoremediation potential of two native plant species in Malaysia, Scirpus grossus and Lepironia articulata by comparing their tolerance and survival of both plants in real crude oil sludge. A preliminary test was conducted to observe whether these two plants could survive in the oily sludge. The growth characteristic of both plants was evaluated by observing the visible symptoms of withering and death of plants throughout a 30-day exposure. S. grossus and L. articulata were exposed to 3 kg of crude oil sludge in 3 L pails under greenhouse conditions. After 30 days of exposure, it was observed that 100% S. grossus could grow and survive in the sludge compared to L. articulate with only 55% survival. As a comparison, S. grossus has more potential to be used in the phytoremediation process of the real crude oil sludge.Â Â Â